Name, translation and cultural transfer in the field of gastronomy - Cantón Rodríguez, María Loreto; López Santiago, Mercedes (Onomázein, 2021)
The tapeo, typical Spanish gastronomic custom, has crossed our frontiers to be settled in numerous parisian eatery establishments. This study aims to analyse a sufficiently large and representative sample of menus that include Spanish tapas offered in premises located in the French capital. After the elaboration of a lexical corpus grouped around the tapas, their ingredients and presentations, the translation techniques used in these documents will be analysed. Indeed, these aperitifs appear totally or partially in their original version, or they are translated into the French language in a more or less picturesque manner, thus expressing the difficulties existing in their translation.